2010
DOI: 10.2527/jas.2009-2668
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary intake and digestibility of teff hay fed to horses1

Abstract: The objective of this study was to evaluate nutrient composition, voluntary DMI, and apparent DM digestibility of teff hay cut at 3 different stages of maturity to evaluate its potential as a preserved forage for horses. Six mature Quarter Horse mares (12 +/- 3 yr; 553 +/- 39 kg of BW) were used in a replicated balanced Latin square design with 3 periods and 3 maturities of teff hay. Eragrostis tef ('Tiffany' teff) was planted in May and harvested at the boot, early-heading, or late-heading stage of maturity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 26 publications
5
26
0
Order By: Relevance
“…Forage nutritive value. Teff crude protein (CP) in this study (Table 3) was consistent with that measured elsewhere (4,6,9,18,19), but greater than that reported by McCown et al (15) and more than sufficient to meet the requirement for maintenance of mature horses when fed a dry matter intake (DMI) of 1.5 to 2.0% of body weight (BW) per day (17). The main effect of irrigation level did not impact CP at any time ( data not shown ) and nitrogen treatment had no effect in the first cutting (Table 3).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Forage nutritive value. Teff crude protein (CP) in this study (Table 3) was consistent with that measured elsewhere (4,6,9,18,19), but greater than that reported by McCown et al (15) and more than sufficient to meet the requirement for maintenance of mature horses when fed a dry matter intake (DMI) of 1.5 to 2.0% of body weight (BW) per day (17). The main effect of irrigation level did not impact CP at any time ( data not shown ) and nitrogen treatment had no effect in the first cutting (Table 3).…”
Section: Resultssupporting
confidence: 90%
“…Timing of the first harvest was based on the initiation of heading by the teff, which has been identified as a preferred stage of maturity by horses (19) and had been approximately 50 to 60 days after planting (DAP) in other studies, with subsequent harvests taken at 30‐ to 35‐day intervals (7,9,18). Standing forage of each entire plot (4.67 × 20 ft) was harvested 16 August, 18 September, and 22 October 2007 and 13 August, 15 September, and 20 October 2008 using a John Deere Model 10 forage chopper, leaving 3‐inch stubble (16,18).…”
Section: Comparing Teff Performance By Irrigation and N Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…DM, ash, ADF and NDF, inclusive of ash, were determined using AOAC procedures ( 62 ) . Apparent digestibility of DM was calculated with the following: DM digestibility = (DMI – faecal output)/DMI ( 63 ) ; calculations were repeated for organic matter, NDF and ADF fractions.…”
Section: Methodsmentioning
confidence: 99%
“…Staniar et al [6] reported dry matter intakes of teff hay between 1.5% and 1.8% for hay harvested at late-heading and boot stages, respectively. These intakes are greater than those found in this study (1.37% of BW).…”
Section: Discussionmentioning
confidence: 97%